Impact of watershed programme on the economy of the Farm households in Andhra Pradesh - B.Nirmala,; G.K.Hiremath, (Journal of Agricultural Extension Management, 2025)
In India, 67 percent of 143 million hectares of arable land which contributes 44 per cent to the food basket and supports 40 per cent of the population, depends on rain. Further, it is estimated that about 450 million bovine population are thriving on rainfed farming. Most of the areas under coarse cereals, oil seeds, cotton and even rice to a little ex tent are under rainfed situation. This indicates the need for substantial efforts both from research and development fronts to meet the increasing demand for food, shelter and  clothing due to the steadily mounting demographic pressure coupled with decreasing ava il ability of per capita cultivable land. It is ironical that even after harnessing all the irrigation water resources (1 13 m. ha.) 50 per cent of cultivable land in India will continue to be rainfed. Hence, management of dry land area assumes prime position in Indi an Agriculture. (ltnal et al. , 1998)